2000
DOI: 10.1258/0022215001904806
|View full text |Cite
|
Sign up to set email alerts
|

Auditory brainstem implant in auditory rehabilitation of patients with neurofibromatosis type 2: Hannover

Abstract: An auditory brainstem implant (ABI) is indicated for patients suffering from bilateral neural deafness. The most affected patients are those with neuro bromatosis type 2 (NF2). An implantation is possible either at the same time as, or after, surgical removal of an acoustic neuroma. This paper demonstrates the results of eight out of 11 patients with NF2, seven of whom received an ABI after tumour removal. Preoperatively, all of them were deaf. Post-operatively, the rst tting served to determine the individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Once implanted with an ABI, there is large variability in outcomes. Interestingly, tumour size does not always relate to ABI outcomes [Lesinski-Schiedat et al, 2000]. Rather, the resulting impact of brainstem compression on the cochlear nuclei may account for the varying ABI outcomes for NF2 patients with different tumour sizes.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Once implanted with an ABI, there is large variability in outcomes. Interestingly, tumour size does not always relate to ABI outcomes [Lesinski-Schiedat et al, 2000]. Rather, the resulting impact of brainstem compression on the cochlear nuclei may account for the varying ABI outcomes for NF2 patients with different tumour sizes.…”
Section: Discussionmentioning
confidence: 98%
“…Bouccara et al, 2007;Lesinski-Schiedat et al, 2000;Matthies et al, 2000]. More favourable ABI outcomes have been reported for NF2 patients with a shorter duration of hearing loss, smaller tumour size, and a higher number of active electrodes [Bouccara et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely to occur due to a continued learning effect following ABI activation. Likewise, several authors indicate that the success of the NF2 patients with hearing loss in rehabilitation is most obvious upon long-term follow-up [20,40]. …”
Section: Discussionmentioning
confidence: 99%
“…Functional results show great variability; from noise perception only to useful speech discrimination in audiovisual mode in a few patients so far. Since the early trials by Hitselberger and House in 1979, as reported by Edgerton et al 13 and Hit sel berger et al, 21 profound improvements in implant array, technology, and speech processing strategies 65 have brought about useful improvement in functional outcome, 4,8,9,17,23,29,31,32,37,42,43,45,46,48,58,59 but still results remain less favorable than in cochlear implants or auditory brainstem implants (ABIs) in patients without NF2. 8 Visionindependent speech perception is not generally achieved.…”
mentioning
confidence: 99%